2020
DOI: 10.17582/journal.pjz/20180709090735
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplementation of Hen Diet with Pennyroyal Extract (Mentha pulegium) on Performance, Egg Quality and Yolk TBARS Values

Abstract: Contribution SCB conceived the idea and supervised the study. AA executed the experiments. SCB and AA performed analytical examinations. SCB wrot the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
1
6
5
1
Order By: Relevance
“…According to Moghadam [ 34 ], the intramolecular hydroxy amine group of choline functions as a decomposer of hydroperoxides by donating an electron, which contributes to reducing lipid peroxidation and protein oxidation in choline-supplemented groups. This response to choline supplementation could result from its role as a methyl donor, which can indirectly increase antioxidant capacity [ 35 , 36 ]. Methionine plays an important role in the synthesis of adenosylmethionine and GSH, which are two important antioxidants [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Moghadam [ 34 ], the intramolecular hydroxy amine group of choline functions as a decomposer of hydroperoxides by donating an electron, which contributes to reducing lipid peroxidation and protein oxidation in choline-supplemented groups. This response to choline supplementation could result from its role as a methyl donor, which can indirectly increase antioxidant capacity [ 35 , 36 ]. Methionine plays an important role in the synthesis of adenosylmethionine and GSH, which are two important antioxidants [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid peroxidation, one of the most important factors affecting eggshell life, is determined by TBARS [ 36 ]. As a result of this study, choline at a concentration of 1500 and 2500 mg/kg resulted in the lowest TBARS value ( p < 0.05), while above these levels TBARS value was negatively affected, except for at the 4000 mg/kg choline level.…”
Section: Discussionmentioning
confidence: 99%
“…Related studies have shown that dietary special substances may have effect on the physiology of laying hens (Celebi 2019;Demir and Kaya 2020), and thus also may effect the quality and the nutritional components of eggs (Wahab et al 2019;Aydin and Bolukbasi 2020;Liu et al 2020;Mahfuz et al 2020). TP can improve health of the body, so it is widely used in livestock and poultry feed.…”
Section: Discussionmentioning
confidence: 99%
“…Yumurta verimi, yumurta ağırlığı, yem tüketimi ve yemden yararlanma oranı gibi performans parametreleri iki haftalık periyotlarda tespit edildi (3). Her tekrardan 4 adet olmak üzere her bir deneme grubundan alınan 28 adet yumurtada yine iki haftalık periyotlarda; şekil indeksi, kabuk kalınlığı, kabuk oranı (4), özgül ağırlık (5), Haugh birimi (6), yumurta sarı rengi, ak ve sarı oranı (7), ak ve sarı indeksi (8) gibi yumurta kalite parametreleri belirlendi. Denemede kullanılan diyetlerin besin madde içerikleri AOAC (9)'de belirtilen analiz yöntemlerine göre yapıldı.…”
Section: Performans Yumurta Kalitesi Ve Kimyasal Analizlerunclassified